Updates on protein-prenylation and associated inherited retinopathies - Ashok, Sudhat; Ramachandra Rao, Sriganesh (Frontiers in Ophthalmology, 2024)
Membrane-anchored proteins play critical roles in cell signaling, cellular architecture, and membrane biology. Hydrophilic proteins are post-translationally modified by a diverse range of lipid molecules such as phospholipids, glycosylphosphatidylinositol, and isoprenes, which allows their partition and anchorage to the cell membrane. In this review article, we discuss the biochemical basis of isoprenoid synthesis, the mechanisms of isoprene conjugation to proteins, and the functions of prenylated proteins in the neural retina. Recent discovery of novel prenyltransferases, prenylated protein chaperones, non-canonical prenylation-target motifs, and reversible prenylation is expected to increase the number of inherited systemic and blinding diseases with aberrant protein prenylation. Recent important investigations have also demonstrated the role of several unexpected regulators (such as protein charge, sequence/protein-chaperone interaction, light exposure history) in the photoreceptor trafficking of prenylated proteins. Technical advances in the investigation of the prenylated proteome and its application in vision research are discussed. Clinical updates and technical insights into known and putative prenylation-associated retinopathies are provided herein. Characterization of non-canonical prenylation mechanisms in the retina and retina-specific prenylated proteome is fundamental to the understanding of the pathogenesis of protein prenylation-associated inherited blinding disorders.